The genetic structure of fermentative vineyard-associated Saccharomyces cerevisiae populations revealed by microsatellite analysis - Schuller, Dorit Elisabeth (2007)
From the analysis of six polymorphic microsatellite loci performed in 361 Saccharomyces cerevisiae isolates 93 alleles were identified, being 52 of them described for the first time. All these isolates have a distinct mtDNA RFLP pattern. They are derived from a pool of 1620 isolates obtained from spontaneous fermentations of grapes collected in three vineyards of the Vinho Verde Region in Portugal, during the 2001 – 2003 harvest seasons. For all loci analyzed, observed heterozygosity was three to four times lower than the expected value supposing a Hardy-Weinberg equilibrium (random mating and no evolutionary mechanisms acting), indicating a clonal structure and strong populational substructuring. Genetic differences among S. cerevisiae populations were apparent mainly from gradations in allele frequencies rather than from distinctive “diagnostic” genotypes, and the accumulation of small allele-frequency differences across six loci allowed the identification of population structures. Genetic differentiation in the same vineyard in consecutive years was of the same order of magnitude as the differences verified among the diferent vineyards. Correlation of genetic differentiation with the distance between sampling points within a vineyard suggested a pattern of isolation-by-distance, where genetic divergence in a vineyard increased with size. The continuous use of commercial yeasts has a limited influence on the autochthonous fermentative yeast population collected from grapes and may just slightly change populational structures of strains isolated from sites very close to the winery where they have been used. The present work is the first large-scale approach using microsatellite typing allowing a very fine resolution of indigenous S. cerevisiae populations isolated from vineyards.